Behavioral characterizations of naivete for time-inconsistent preferences - David S. Ahn; Ryota Iijima; Yves Le Yaouanq; Todd Sarver (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We propose nonparametric definitions of absolute and comparative naivete. These definitions leverage ex-ante choice of menu to identify predictions of future behavior and ex-post (random) choices from menus to identify actual behavior. The main advantage of our definitions is their independence from any assumed functional form for the utility function representing behavior. An individual is sophisticated if she is indifferent ex ante between retaining the option to choose from a menu ex post or committing to her actual distribution of choices from that menu. She is naive if she prefers the flexibility in the menu, reflecting a mistaken belief that she will act more virtuously than she actually will. We propose two definitions of comparative naivete and explore the restrictions implied by our definitions for several prominent models of time inconsistency.
Keywords: 330; Naive; sophisticated; time inconsistent; comparative statics